2017
DOI: 10.1002/bjs.10330
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of therapeutic strategies for bleeding injury on early survival, transfusion needs and correction of coagulopathy

Abstract: A high platelet or plasma to RBC ratio, and use of tranexamic acid were associated with a decreased need for massive transfusion and increased survival in injured patients with bleeding. Early normalization of coagulopathy was not seen for any transfusion ratio, or for use of tranexamic acid or fibrinogen products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 32 publications
(29 reference statements)
4
39
0
2
Order By: Relevance
“…In 2013, Holcomb et al 20 published findings of the PROMMTT (Prospective, Observational, Multicenter, Major Trauma Transfusion) study showing that although only 72% of patients received platelets within 3 hours, the early delivery of higher platelet and plasma ratios was associated with decreased 24-hour mortality. Similar conclusions were drawn from the ACIT (Activation of Coagulation and Inflammation in Trauma) study, where Balvers et al 21 reported higher ratios of platelets or plasma/RBCs, in combination with tranexamic acid, reduced both the rate of massive transfusion and the incidence of mortality in a comparable patient population. Furthermore, in the PROPPR (Pragmatic, Randomized Optimal Platelet and Plasma Ratios) trial, a significant increase in the incidence of hemostasis and a reduction in exsanguinating deaths were found in patients receiving a higher ratio of platelets and plasma/RBCs.…”
Section: Introductionsupporting
confidence: 70%
“…In 2013, Holcomb et al 20 published findings of the PROMMTT (Prospective, Observational, Multicenter, Major Trauma Transfusion) study showing that although only 72% of patients received platelets within 3 hours, the early delivery of higher platelet and plasma ratios was associated with decreased 24-hour mortality. Similar conclusions were drawn from the ACIT (Activation of Coagulation and Inflammation in Trauma) study, where Balvers et al 21 reported higher ratios of platelets or plasma/RBCs, in combination with tranexamic acid, reduced both the rate of massive transfusion and the incidence of mortality in a comparable patient population. Furthermore, in the PROPPR (Pragmatic, Randomized Optimal Platelet and Plasma Ratios) trial, a significant increase in the incidence of hemostasis and a reduction in exsanguinating deaths were found in patients receiving a higher ratio of platelets and plasma/RBCs.…”
Section: Introductionsupporting
confidence: 70%
“…This is also in line with the iTACTIC protocol [167]. In severe traumatic hemorrhage, fixed-ratio RBC and plasma transfusion is not effective to treat ATC and to reduce mortality [12][13][14][15][16][17]171]. Innerhofer et al compared in their RCT the efficacy of ROTEM-guided administration of coagulation factor concentrates (fibrinogen, factor XIII, and four-factor PCC) versus plasma transfusion to treat ACT and to stop bleeding [172,173].…”
Section: In Trauma and Orthopedic Surgerymentioning
confidence: 79%
“…Ratio-based transfusion concepts do not correct coagulopathy and do not reduce mortality in patients with severe hemorrhage [13][14][15][16][17]. Ratio-based concepts do not stop bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Different definitions of hyperfibrinolysis as detected by VMs used in various studies have been reviewed and summarized elsewhere , and efforts are underway to standardize how diagnosis is performed, and to identify the best parameters to guide therapeutic interventions. For example, research is being carried out by the European TACTIC consortium to develop data‐driven algorithms for the management of hemorrhage .…”
Section: Viscoelastic Methodsmentioning
confidence: 99%